Artistic Phenomenon of the Danube Poet Vladimir Reva: Array - Reva-Lievshakova, Lyudmila (Journal of Danubian Studies and Research, 2020)
The article deals with the artistic phenomenon of the famous poet Bessarabia Vladimir Reva. The material of the study was the poetry of seven collections of the author, published in different years. A peculiar analysis of artistic and literary features and creative ideas that the author embodied in his poetic works is offered.